Kyai's Leadership Style in Forming the Independence of Santri - Chusnul Chotimah; Mohammad Febri Irawan Saputra (SCHOOLAR: Social and Literature Study in Education, 2023)
This study discusses the Kyai's leadership style in improving the quality of Islamic education by forming independent students. Like those at Al-Falah Islamic Boarding School Bahrul Ulum Tambakberas Jombang, students at Al-Falah Islamic Boarding School in all aspects of needs within the scope of Islamic boarding schools, almost all of them are run by Santri independently. Therefore the author raises the theme "Kiai's leadership style in forming the independence of students at the Al-Falah Islamic Boarding School Bahrul Ulum Tambakberas, Jombang". The author uses a descriptive qualitative research type, by conducting observations, interviews, and documentation at the Al-Falah Bahrul Ulum Tambakberas Islamic Boarding School, Jombang, so that the conclusion is found; The leadership style used by K. Azam Choiruman Najib at the Al-Falah Islamic Boarding School Bahrul Ulum Tambakberas is a guided democratic leadership style, namely a leadership style that uses a style that is willing to accept opinions from subordinates in order to achieve common goals by means of a leadership approach based on strong ethical and moral principles. Then the supporting factors in establishing the independence of the Al-Falah Bahrul Ulum Tambakberas Jombang Islamic Boarding School students include 1) The management of Al-Falah Bahrul Ulum Tambakberas Jombang Islamic Boarding School students is formed, 2) The construction of supporting facilities for students' independence in the form of kitchens, cooperatives, and others, 3) There is control of the students' pocket finances by the financial administrator. The inhibiting factors in forming the independence of the students of the Al-Falah Bahrul Ulum Tambakberas Jombang Islamic Boarding School include 1) the emergence of rules from administrators that limit students, 2) The performance of the management is not optimal, 3) The students are often spoiled by their parents, 4) The students' lack of self-awareness, 5) The lack of interest in learning.